Knowledge of warfarin among patients on warfarin therapy, using anticoagulant knowledge assessment tool, in Patan Hospital - Das, Sunil Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Warfarin is commonly used to prevent and treat cardiac, thromboembolic, and hypercoagulable conditions Despite its benefits, it was one of the top ten drugs with the most serious adverse events reported to the FDA during the 1990s and 2000s. Warfarin’s narrow therapeutic window necessitates careful management to avoid bleeding from over-anticoagulation or thrombosis from under-anticoagulation. Various tools exist to assess patient knowledge of warfarin, including the validated Anticoagulation Knowledge Assessment (AKA) questionnaire. This study uses the AKA tool to evaluate warfarin knowledge among patients at Patan Hospital, Lalitpur, Nepal. Method: It was a single center, cross-sectional study done among 85 patients. Study was done for one year from Nov 2020 to Oct 2021. Convenient sampling was employed. The Anticoagulation Knowledge Assessment (AKA) questionnaire was translated into Nepali, modified for local relevance, and validated. Adequate knowledge was defined as correctly answering at least 70% of the questions. Result: The study included 85 participants, 54 (63.5%) male and 31 (36.5%) female, with a mean age of 40.5 years (range: 16-91 years). Majority of participants attended primary level education 27 (31.8%). Only 17.6% of participants demonstrated adequate knowledge of warfarin, with a higher proportion of males (12) than females (3). Adequate knowledge was significantly associated with education level, but not with sex or age. Conclusion: The analysis revealed that 17.6% of patients had adequate knowledge of warfarin. Education level showed a significant association with knowledge, with a p-value of 0.002.